The Influence of Ar Rahn Financing, Income (Ujrah), Number of Customers, Gold Price Fluctuations and Inflation Rates on the Profitability of Islamic Pawnshops in Indonesia in 2019-2023 - Ade Febrinanda Susilowati; Suwignyo Widagdo; Muhammad Rijalus Sholihin (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This study aims to analyze the effect of Ar-Rahn financing, income (Ujrah), number of customers, gold price fluctuations, and inflation rates on profitability. The population in this study is Islamic pawnshops registered with the Financial Services Authority in 2019-2023. This study uses a sampling technique, namely the methodSaturation Samplingand using monthly data, so that a sample of 3 companies was obtained with a total of 60 data samples. The data analysis method used multiple linear regression analysis using IBM SPSS Statistics 25. The results of the study showed that partially the Ar-Rahn financing variables, number of customers, and audit gold price fluctuations did not affect profitability. While the Ujrah income and inflation rate variables affected profitability. Simultaneously, the Ar-Rahn financing variables, Ujrah income, number of customers, gold price fluctuations, and inflation rates affected profitability